An approach to the highway alignment development process using genetic algorithm based optimisation - Ahmad Al-Hadad, Botan (2011)
Highway alignment development is recognised as a non-linear constrained optimisation problem. It is affected by many economical, social, and environmental factors subject to many design constraints. The highway alignment development process is therefore considered complex but very important.